ANOTHER APPROACH TO COMPLEX INTEGRATION - Tutschke, W. (Matematichki Bilten, 1997)
In this short note we are going to show that the concept of associated differential operators can be used in order to invert complex differential operators by complex line integrals not depending on the path of integration.